ACCELERATING DIGITAL ADMINISTRATIVE TRANSFORMATION TO ACHIEVE AGILE PUBLIC SERVICES AT DR. MOHAMMAD ZYN REGIONAL HOSPITAL - Mareta Jaya Rukmi, Ika; Nihayatus Sholicah; Widyawati (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes the strategies for accelerating digital administrative transformation to achieve public service agility at RSUD dr. Mohammad Zyn, Sampang Regency. In the era of technological disruption, shifting from conventional bureaucracy to progressive digital governance is essential to eliminate bureaucratic hurdles such as long queues and unclear medical schedules. The research focuses on evaluating how digital leadership and digital inclusivity transform the hospital into a more agile, responsive, and humanistic organization. Using a qualitative descriptive method, data were gathered through participatory observation, in-depth interviews, and documentation studies involving informants from management to service users. The findings indicate that the success of digital transformation is heavily determined by digital leadership's capacity to mitigate internal resistance. Leaders act as catalysts by transforming employee appreciation into support through re-skilling, psychological incentives, and debureaucratization that simplifies data input procedures. Furthermore, organizational agility improves when technology is positioned as a tool to refocus medical personnel on patient care rather than administrative burdens. Externally, the study highlights the importance of digital inclusivity in bridging the digital divide within the local community, addressing systemic barriers such as linguistic hurdles for agrarian populations, lack of accessibility for people with disabilities, and logistical challenges in rural areas. Ultimately, healthcare service agility at RSUD dr. Mohammad Zyn is achieved through a holistic approach that synchronizes technological sophistication with human resource readiness and inclusive design standards. Digitalization serves not merely as a physical modernization but as a primary driver for creating sustainable public value for all citizens.